(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: Today, new opportunities are being created for the further development of musical art and culture in Uzbekistan. Searching for young talents in various areas of music culture, taking care of their creative activities has become one of the most important tasks. This article explains the importance of Uzbek music in the past and present in raising the spiritual level of our people, the fact that music is one of the leading factors in the social development of the new Uzbekistan, and the processes of formation of Uzbek music culture.